Differentiation of advanced generation mutant wheat lines: Conventional techniques versus Raman spectroscopy - SEN, Ayse; Kecoglu, Ibrahim; Ahmed, Muhammad; Parlatan, Ugur; Unlu, Mehmet Burcin (Frontiers in Plant Science, 2023)
This study was conducted to evaluate the potential for the use of Raman Spectroscopy in plant breeding programs.For this purpose, the evaluation of the mutant population constructed by the application of 4 mM NaN3 to the somatic embryos obtained from mature wheat (Triticum aestivum L. Adana-99 cv.) embryos. The evaluation of the advanced generation wheat mutants, which were brought up to the seventh generation with salt stress tolerance by following in vitro and in vivo environments, were evaluated using conventional techniques (measurement of antioxidant enzyme activities (SOD, CAT and POX), total chlorophyll, TBARS and proline contents, measurement of the concentration of Na+ and K+ ions, evaluation of gene expression by qPCR (TaHKT2;1, TaHKT1;5, TaSOS1, TaNa+/H+ vacuolar antiporter, TaV-PPase, TaV-ATPase, TaP5CS) and Raman Spectroscopy. In this study, there was no significant difference in the increase of SOD, CAT and POX antioxidant enzyme activities between the salt-treated and untreated experimental groups of the commercial cultivar, while there was a statistically significant increase in salt treated advanced generation mutants as compared to control and salt treated commercial cultivar. Proline showed a statistically significant increase in all experimental groups compared to the untreated commercial cultivar. The degradation in the content of chlorophyll was lower in the salt treated advanced generation mutants than in the salt treated commercial cultivar. According to gene expression studies, there were statistical differences at various levels in terms of Na+ and/or K+ uptake from soil to plant (TaHKT2;1, TaHKT1;5 and TaSOS1) and Na+ compartmentalize into cell vacuol (TaNa+/H+ vacuolar antiporter, Ta vacuolar pyrophosphatase, Ta vacuolar H+-ATPase). The expression activity of TaP5CS, which is responsible for the transcription of proline, is similar to the content of proline in the current study. As a result of Raman Spectroscopy, the differences in peaks represent the protein-related bands in mutants having a general decreasing trend in intensity when compared to commercial cultivar. Amide-I (1630, 1668 cm-1), Histidine, Lysine, Arginine and Leucine bands (823, 849, 1241, 1443, 1582 cm-1) showed decreasing wavenumbers. Beta carotene peaks at 1153 and 1519 cm-1 showed increasing trends when the normalized Raman intensities of the two mutant lines were compared.